Association of total cholesterol and HDL-C levels and outcome in coronary heart disease patients with heart failure. Issue 9 (March 2017) - Zhao, Qin; Li, Jianfei; Yang, Jin; Li, Rongshan
Abstract : Abstract: The aim of the study was to evaluate associations of total cholesterol (TC) and high density lipoprotein cholesterol (HDL-C) levels with prognosis in coronary heart disease (CHD) patients with heart failure (HF). Patients who were angiographical-diagnosis of CHD and echocardiographical-diagnosis of left ventricular ejection fraction (LVEF) < 45% were enrolled. Baseline characteristics were collected and association of TC and HDL-C levels with rehospitalization for HF and all-cause mortality was assessed. A total of 118 patients were recruited. Mean age was 58.6 ± 10.9 years and male accounted for 65%. Mean LVEF was 39.5 ± 4.0%. Twenty-eight patients were rehospitalized for HF and 6 patients were dead. In patients with poor prognosis, lower body mass index (BMI), TC, HDL-C and albumin while higher high sensitivity C-reactive protein (Hs-CRP) was observed. TC was positively correlated with BMI and albumin, and HDL-C was inversely correlated with Hs-CRP. The associations of TC level and rehospitalization for HF and all-cause mortality were attenuated but consistently significant through model 1 to 4, with odds ratio (OR) of 0.97 (95% confidence interval [CI]: 0.92–0.99). Associations of HDL-C level and rehospitalization for HF and all-cause mortality were also consistently significant through model 1 to 4, with OR of 0.95 (95% CI: 0.90–0.98). Strength of association was attenuated prominently in model 3 after adjusted for Hs-CRP, and no change was observed after further adjusted for BMI and albumin. Higher baseline TC and HDL-C levels are associated with better outcome in CHD patients with HF.